Peningkatan Kompetensi Mahasiswa Melalui Pelatihan Penulisan Karya Ilmiah Dengan Menggunakan Metode Kualitatif Dalam Masa Pandemi Covid-19 - Tri Handayani Amaliah (Jurnal Ilmiah Pangabdhi, 2021)
The current reality shows that there are many opportunities for scientific writing competitions for students, but there are still very few students who are interested in participating in these activities. This is due to a lack of self-confidence and student interest in participating in competitions. The objectives of the implementation of this service program are: 1) to educate students from an early age about qualitative research methods; 2) to improve the ability of early semester students in and preparation of scientific papers. The method used in this service program is the lecture method, the discussion / question and answer method and ends with an evaluation. Due to the current outbreak of COVID-19, the training method is carried out online. The implementation phase of the training was carried out on May 11, 2021, attended by 126 accounting students in the second and fourth semesters. At the end of the training stage, an evaluation is carried out to measure the level of student understanding of the training that is followed. The results of the evaluation showed that the training was carried out effectively. This is shown through the questionnaires distributed after attending the training, as many as 72.5% of the training participants stated that the preparation of scientific papers using qualitative methods was very easy to do, as many as 60% were interested in participating in scientific writing competitions in the future. 99.2% of the trainees are interested in learning more about scientific works that have been published and 100% of students are interested in further deepening their knowledge of qualitative research methods.